A Study on Inventory Control of Soybean as Raw Material in â€œTakwaâ€ Tofu Industry Using The Fixed Order Quantity Method - Dania, Wike Agustin Prima; Effendi, Usman; Nurika, Irnia (Jurnal Teknologi Pertanian, 2005)
An inventory control of raw material in an industry is important to minimize the total cost. The objective of this research was to control the inventory of soybean as the main raw material in a tofu industry using the Fixed Order Quantity Method. The method was employed to determine the optimal quantity order, safety stock, reorder point, and to optimize the total inventory cost. The calculations were made based on the available records of the product demand of the previous year, and an estimation was performed for the following year. The results showed that the estimated cost associated with inventory for one year ahead were Rp. 114,767,466.50 of purchasing cost, Rp. 114,794.38 of ordering cost, Rp. 122,609.28 of holding cost and Rp. 186.05 of shortages cost. The respective optimal values of quantity order, reorder point, and safety stock were 1,324.12 kg, 14.52 kg, and 43.92 kg, thus the total cost was Rp 115,005,056.20. The implementation of the method was able to reduce the inventory cost by Rp. 286,595.72 in a year. The sensitivity analysis, if the demand and price of soybean changes, showed that 10 % up or 10 % down of the parameters would not likely affect the optimal quantity and inventory total cost. Key words: inventory control, Fixed Order Quantity, cost, tofu industry